Impact of Training Modules on Physicians’ Perspective of COVID-19: An Online Survey - Umar, Badar Uddin; Alam, Nazmun Nahar; Alam, Tanbira; Mannan, Mahmudul; Rahman, S M Niazur (Journal of Medicine, 2021)
Background: The outbreak of COVID-19 has remained a massive challenge for healthcare workers specially physicians. Effective professional training has a crucial role in preparing doctors for responding to pandemics. Objective: To assess the effectiveness of existing training modules on enhancing knowledge, ensuring safe practice, and improving behavior on COVID-19 among physicians. Methods: This is a descriptive, cross-sectional, online survey; where a virtual questionnaire was used to collect data through online professional platforms. A pre-tested survey tool was employed to assess the impact of professional training on infection prevention and control. Results: Total 161 physicians participated in this survey from 15 different countries. Most of the respondents (72%) received training from various sources like the workplace (60%) and international agencies (21%), through the in-person or online format. Knowledge assessment revealed advanced (43%) and competent (40%) understanding by the participants. Improving knowledge progression was displayed by the cohort who received professional training (p<0.00). Physicians’ positive behavior and good practices were observed with the training modules. Conclusion: It became evident from this study, that professional training is effective in enhancing knowledge, improving behavior, and ensuring safe practices. Hence, designing such training modules for the physicians is warranted to tackle ongoing and future pandemics. J MEDICINE 2021; 22: 107-113